1994
DOI: 10.1021/bi00173a013
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Aspartate-85 with a Water Molecule and the Protonated Schiff Base in the L Intermediate of Bacteriorhodopsin: A Fourier-Transform Infrared Spectroscopic Study

Abstract: Fourier-transform infrared spectra were recorded at 170 K before and after irradiating the Asp85-->Asn mutant of bacteriorhodopsin. The difference spectrum exhibits protein bands such as those due to the perturbations of Asp96 and Asp115 and the N-H stretching vibration of tryptophan, characteristic of the L minus all-trans-bacteriorhodopsin spectrum of the wild-type protein. However, some vibrational bands of the peptide backbone and the chromophore are different from L and more characteristic of N of the wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 114 publications
(118 citation statements)
references
References 48 publications
8
110
0
Order By: Relevance
“…This feature which was initially discovered in studies of L at 170 K and M at 230 K (48) is observed as a depletion band upon formation of L at 298 K, and this feature persists in M and N. This band is also the same one that was recently detected in static difference spectra, obtained using an in situ H 2 16 O/ H 2 18 O exchange technique with BR at room temperature (37). In the H 2 16 O/ H 2 18 O exchange measurements, the band was not observed in D85N (37) and it was also not observed in the light-induced difference spectrum of the D85N mutant at 170 K (25). As discussed previously (37,49) this water vibration is very likely due to the free O-H bond of Wat401 in BR, a water whose other hydrogen interacts with Asp85 (i.e., Asp85-COO − ••H-O-H), as is seen in the crystal structure of BR (50).…”
Section: Water Forms H-bonds With Asp85 In L M and N At 298 Ksupporting
confidence: 83%
“…This feature which was initially discovered in studies of L at 170 K and M at 230 K (48) is observed as a depletion band upon formation of L at 298 K, and this feature persists in M and N. This band is also the same one that was recently detected in static difference spectra, obtained using an in situ H 2 16 O/ H 2 18 O exchange technique with BR at room temperature (37). In the H 2 16 O/ H 2 18 O exchange measurements, the band was not observed in D85N (37) and it was also not observed in the light-induced difference spectrum of the D85N mutant at 170 K (25). As discussed previously (37,49) this water vibration is very likely due to the free O-H bond of Wat401 in BR, a water whose other hydrogen interacts with Asp85 (i.e., Asp85-COO − ••H-O-H), as is seen in the crystal structure of BR (50).…”
Section: Water Forms H-bonds With Asp85 In L M and N At 298 Ksupporting
confidence: 83%
“…Asp-85 is located near the Schiff base and serves as the counterion. The presence of water molecules in this region had been suggested by Fourier transform infrared (FTIR) studies (4,5), and these were later confirmed as W401, W402, and W406 in the high resolution crystal structure of the BR ground state (PDB code 1C3W; see Fig. 1) (6).…”
Section: Bacteriorhodopsin (Br)mentioning
confidence: 81%
“…However, the crystal structure shows a water molecule in the vicinity of the FMN chromophore (7). It has been demonstrated that in bacteriorhodopsin structural water is required to stabilize the protein and participates in intramolecular proton transfer reactions during the proton-pumping photocycle (32,33). This water itself could be either the proton donor/acceptor group, or it could act as a bridge between the cysteine and another remote amino acid side chain that donates/accepts the proton.…”
Section: Protein-chromophore Interactions In the Lov2 Groundmentioning
confidence: 99%